Personas goda un cieņas aizsardzības efektivitāte vārda brīvības nodrošināšanas ietvaros - Eihmane, Elīna (Latvijas Universitāte, 2006)
Both, reputation and freedom of speech are constitutional rights. But whether we want it or not, they regularly meet and are in conflict with one to another. But, as many judgments show, courts rather rarely reach a judgment, what is excellent within its juridical construction. That’s why the target of this job was to examine as many judgments it’s possible and to inspect cases of defamation in the U.S.A. (as it has the most higher degree of speech protection, after Sullivan case), together with the praxis of the European Court of Human rights and of national courts. Author wanted to create a test for the courts. This work consists of seven main chapters. The second one looks at the statutory regulation about reputation and freedom of speech. The next – what is absolute and qualified privileges (for Latvian jurisdiction has no similar concept), fourth will go on and try to define different possible status of persons; fifth will examine, how an opinion might be defended; sixth will consider about factual basis and standards of liability, but the last chapter will lay down the borders to criticize persons. Finally, the test is built up from three categories of criteria – id est it includes the public interest, what varies from political questions till just private. Then, the test weighes out, whether the factual basis is true and if not, what kind of liability (malice, actual malice, bona fide) is to apply, taking into account, what is the status of the defamed person – public official, public figure, quasi-public official figure or private person. So, the most ample protection is intended for a private person (even strict liability), but the less – for public official/figure. But the protection of opinion varies from the status of the person and the interest the case involved.
Efficiency of the protection of persons honour and dignity within the framework of respect for the freedom of speech
Keywords: Tiesības